Fetal and neonatal alloimmune thrombocytopenia: recommendations for evidence‐based practice, an international approach. (3rd March 2019) - Lieberman, Lani; Greinacher, Andreas; Murphy, Michael F.; Bussel, James; Bakchoul, Tamam; Corke, Stacy; Kjaer, Mette; Kjeldsen‐Kragh, Jens; Bertrand, Gerald; Oepkes, Dick; Baker, Jillian M.; Hume, Heather; et al.
Abstract: Fetal and neonatal alloimmune thrombocytopenia (FNAIT) may result in severe bleeding, particularly fetal and neonatal intracranial haemorrhage (ICH). As a result, FNAIT requires prompt identification and treatment; subsequent pregnancies need close surveillance and management. An international panel convened to develop evidence‐based recommendations for diagnosis and management of FNAIT. A rigorous approach was used to search, review and develop recommendations from published data for: antenatal management, postnatal management, diagnostic testing and universal screening. To confirm FNAIT, fetal human platelet antigen (HPA) typing, using non‐invasive methods if quality‐assured, should be performed during pregnancy when the father is unknown, unavailable for testing or heterozygous for the implicated antigen. Women with a previous child with an ICH related to FNAIT should be offered intravenous immunoglobulin (IVIG) infusions during subsequent affected pregnancies as early as 12 weeks gestation. Ideally, HPA‐selected platelets should be available at delivery for potentially affected infants and used to increase the neonatal platelet count as needed. If HPA‐selected platelets are not immediately available, unselected platelets should be transfused. FNAIT studies that optimize antenatal and postnatal management, develop risk stratification algorithms to guide management and standardize laboratory testing to identify high risk pregnancies are needed.